Effect of Habitat Types on Breeding Bird Assemblages in the Sidi Reghis Forests (Oum El Bouaghi, North-Eastern Algeria) - Chouaib Rebbah, A; Menaa, M; Telailia, S; Saheb, M; Maazi, M.C. (My University, 2019)
This study was set in three forest habitats of Sidi Reghis Mountain within the province of Oum El Bouaghi (north-eastern Algeria). We conducted the first bird survey in this area using the point count method to describe the composition of woodland breeding avifauna and to analyze the spatial distribution among habitat types (oak woodlands, pine woodlands and oak-pine mixed woodlands). A total of 69 species were observed. One species was recorded only in mixed oak-pine forests, six were found exclusively in oak woodlands and 17 species were found only in pine woodlands. We noted 20 protected species, only one endangered species, and five endemic species to the Maghreb and/or to North Africa. The presence of these species with patrimonial value reinforces the importance of the conservation of Sidi Reghis avifauna. Bird abundance, species richness and species diversity were significantly higher in pure pine woodlands than in mixed oak-pine and oak forests. According to PERMANOVA and ANOSIM tests, and the NMDS plot, the avian assemblages of Sidi Reghis Mountain varied significantly between different habitats. Further, SIMPER test indicated that six of the seven species were responsible for the mean of 50% of dissimilarity between sampled habitats. The dissimilarity between pine woodlands and mixed oak-pine forests was about 50%, in general, and produced by differences in abundance of Common Chaffinch Fringilla coelebs, European Serin Serinus serinus, House Sparrow Passer domesticus, European Greenfinch Chloris chloris, Spotted Flycatcher Muscicapa striata, and Common Blackbird Turdus merula. The differences between pine woodlands and oak woodlands (about 60%) and oak-pine mixed woodlands and oak woodlands (about 50%) were mainly produced by species that were present in just one sampled area, most with preference for pine woodlands. The differences related to pine woodlands are the results from Moussier’s Redstart Phoenicurus moussieri and European Turtle Dove Streptopelia turtur presence.